Structural insights into the action mechanisms of artificial electron acceptors in photosystem II - Kamada, Shinji; Nakajima, Yoshiki; Shen, Jian-Ren (The Journal of biological chemistry, 2023)
Photosystem II (PSII) utilizes light energy to split water, and the electrons extracted from water are transferred to QB, a plastoquinone molecule bound to the D1 subunit of PSII. Many artificial electron acceptors (AEAs) with molecular structures similar to that of plastoquinone can accept electrons from PSII. However, the molecular mechanism by which AEAs act on PSII is unclear. Here, we solved the crystal structure of PSII treated with three different AEAs, 2,5-dibromo-1,4-benzoquinone, 2,6-dichloro-1,4-benzoquinone, and 2-phenyl-1,4-benzoquinone, at 1.95 to 2.10 Å resolution. Our results show that all AEAs substitute for QB and are bound to the QB-binding site (QB site) to receive electrons, but their binding strengths are different, resulting in differences in their efficiencies to accept electrons. The acceptor 2-phenyl-1,4-benzoquinone binds most weakly to the QB site and showed the highest oxygen-evolving activity, implying a reverse relationship between the binding strength and oxygen-evolving activity. In addition, a novel quinone-binding site, designated the QD site, was discovered, which is located in the vicinity of QB site and close to QC site, a binding site reported previously. This QD site is expected to play a role as a channel or a storage site for quinones to be transported to the QB site. These results provide the structural basis for elucidating the actions of AEAs and exchange mechanism of QB in PSII and also provide information for the design of more efficient electron acceptors.